1991
DOI: 10.1172/jci115034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the metabolism of plasma low density lipoproteins in healthy males.

Abstract: The plasma concentration of the atherogenic low density lipoproteins (LDL) increases with age. To clarify the mechanism of this change, we studied the kinetics of autologous '25I-LDL apolipoprotein B (apo B) in 41 normolipidemic, nonobese healthy males. For comparison, they were divided into three age groups: young, 21-39 yr (n = 18), middle-aged, 40-59 yr (n = 11), and old, 60-80 yr (n = 12). The levels of plasma LDL cholesterol and LDL apo B increased from respectively 3.4±0.1 (SEM) mmol/liter and 86±2 mg/dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
0
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 41 publications
11
97
0
6
Order By: Relevance
“…Based on their reported menses, these subjects were further divided into three groups ( 23 ): follicular phase (days 1-11), ovulation phase (days [12][13][14][15][16][17][18], and luteal phase (days [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. As expected, the E2 level was highest at ovulation ( Fig.…”
Section: Serum Lipoproteins and Pcsk9 Levels Change During The Menstrmentioning
confidence: 99%
“…Based on their reported menses, these subjects were further divided into three groups ( 23 ): follicular phase (days 1-11), ovulation phase (days [12][13][14][15][16][17][18], and luteal phase (days [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. As expected, the E2 level was highest at ovulation ( Fig.…”
Section: Serum Lipoproteins and Pcsk9 Levels Change During The Menstrmentioning
confidence: 99%
“…A progressive relative lack of GH may also underlie the known reduction in LDL clearance that occurs with ageing. 38 The present studies provide novel information on the regulation of circulating PCSK9 during basal physiological conditions. From our data, the hypothesis emerges that during the diurnal phases and after fasting, dynamic changes of the level of hepatic cholesterol regulate the expression of HMGCoA reductase, PCSK9, and LDLRs.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, LDL-cholesterol increased with age, from 3·37 in the young, to 3·76 in the middle aged and to 4·05 mM/l in the old aged. Additionally, VLDLcholesterol has been observed to either remain steady or increase with age, while HDL-cholesterol appears to be unaffected by the ageing process (58,59) . Abbott et al also found sex influences the lipoprotein profile.…”
Section: Intrinsic Ageingmentioning
confidence: 99%